PENERAPAN MEDIA BENDA KONKRET PADA PEMBELAJARAN BANGUN DATAR DI KELAS 2 - Zurmida Dwi Nazulfah; Achmad Fanani; Cholifah Tur Rosidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study's goal is to learn how to use concrete object media in class 2. This depends on educators who have not involved substantial article media in learning science. So the scientist expects to help educators in the use of substantial item media by presenting a proposal research named